Nutritional intervention in older adults with type 2 diabetes mellitus to achieve glycemic control - Jessica Gabriela Arévalo Berrones; Keylee Alexandra Cevallos Paredes; María de los Ángeles Rodríguez Cevallos (Revista Cubana de Medicina Militar)
Introduction: Diabetes mellitus is a chronic disease that generates a large number of systemic complications, mainly in the geriatric population. Metabolic control is vital to control the disease. Maintaining an adequate nutritional balance is essential. Objective: To identify the effect of a nutritional education intervention on glycemic control in older adults diagnosed with type 2 diabetes mellitus. Methods: Applied research with a quasi-experimental design and mixed approach, which included 73 older adults with a diagnosis of type 2 diabetes mellitus. The nutritional status of older adults was identified and an educational intervention was applied. The glycemic level was determined before the intervention and after its application. The McNemar test was applied to identify the significance of the changes in the glycemic control of the patients. Results: Average age was 67.38 years; patients were between 60 and 69 years (47.94%), female (73.97%) and with the presence of comorbidities (83.56%) predominated. 36.99% of the patients had inadequate glycemic control at the beginning of the investigation. 49.32% had excess nutritional disorders and 67.75% of them had a low level of knowledge. Conclusions: The applied nutritional intervention favored glycemic control in older adults with a diagnosis of type 2 diabetes mellitus included in the research. Likewise, the percentage of patients with nutritional alterations due to excess improved and the level of knowledge of the investigated patients increased.